Anthracyclines: a cornerstone in the management of non-Hodgkin’s lymphoma - Stefano Luminari; Antonella Montanini; Massimo Federico (Hematology Reports, 2011)
Since anthracyclines were introduced in the treatment of non-Hodgkin’s lymphoma in the late 1960s, they have been acknowledged as a cornerstone in the management of the disease and, in particular, of aggressive lymphomas. The high efficacy of anthracycline-containing regimens must, however, be balanced against the drug-related toxicity, which mainly affects the cardiovascular system and represents a major concern for clinicians, especially in the treatment of elderly patients. Patients’ outcomes could be further improved, particularly for those at high risk of cardiotoxicity, by substituting liposomal doxorubicin for conventional doxorubicin. This approach has already been tested and shown to be effective in several cancers, especially in different subsets of patients with diffuse large B-cell lymphoma. The use of liposomal doxorubicin in combination regimens for other conditions, such as follicular lymphoma and splenic marginal zone lymphoma, is also under investigation, and early results are promising.